2011
DOI: 10.1177/0093854810388160
|View full text |Cite
|
Sign up to set email alerts
|

Suspect Mental Disorder and Police Use of Force

Abstract: It has been suggested that the police tend to respond to the unusual behaviors of mentally disordered individuals with coercive tactics that should be reserved for criminal offenders, such as arrest. Although recent research tested, and rejected, this perspective regarding arrest decisions, the present study investigated the most coercive form of police authority, the use of force. Using officer self-report data from two municipal law enforcement agencies, the present study investigated whether mentally disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 38 publications
6
58
1
1
Order By: Relevance
“…Even after controlling for resistance and possession of a weapon, persons who were judgmentally impaired were more likely to experience police use-of-force. On the contrary, Johnson (2012) found that police do not treat individuals with mental disorders more harshly, but people who are mentally unstable are significantly more likely to physically resist, assault officers, and possess a weapon. Therefore, officers are "influenced most by the violence threat and level of resistance they encounter" (p. 141).…”
Section: Overview Of Individual and Situational Correlates Of Police mentioning
confidence: 97%
See 1 more Smart Citation
“…Even after controlling for resistance and possession of a weapon, persons who were judgmentally impaired were more likely to experience police use-of-force. On the contrary, Johnson (2012) found that police do not treat individuals with mental disorders more harshly, but people who are mentally unstable are significantly more likely to physically resist, assault officers, and possess a weapon. Therefore, officers are "influenced most by the violence threat and level of resistance they encounter" (p. 141).…”
Section: Overview Of Individual and Situational Correlates Of Police mentioning
confidence: 97%
“…The uncertainty officers often face after any use-of-force is magnified in SbC cases where subjects often are highly emotional or have mental illness (Johnson, 2012). Family members of the subjects and the public often judge the officers, questioning the need for them to use lethal force.…”
Section: Introductionmentioning
confidence: 99%
“…similarly, terrill's examinations (terrill, 2005;terrill & Mastrofski, 2002) of police-suspect encounters found that behavioral indications of mental impairment did not influence the severity of police use of force after controlling for suspect demeanor and substance intoxication. similarly, Johnson (2011) found that police reported using more severe levels of force on suspects who appeared "mentally unstable"; however, this relationship was not statistically significant after taking into account other pertinent factors including violent behavior and possession of weapons. it seems, therefore, that the use of more severe force on persons who appear mentally disordered is being justified because of more aggressive behavior being displayed during the encounter.…”
Section: The Impact Of Mental State On Use Of Forcementioning
confidence: 93%
“…Given the very complex nature of police encounters with people in mental health crisis (Clifford 2010), and statistically significant increased likelihood that police use more severe force on people who they perceive to be mentally ill (Johnson 2011, Kesic et al 2013b, police use of force guidelines clearly need more nuanced consideration (Bronitt and Gani 2012). To propose a more tailored approach to the de-escalation of mental health crisis encounters, we now consider the approach to de-escalation and limitsetting widely accepted as core business in inpatient mental health settings to discern if and how these core principles could be applied to, and help inform, the policing context.…”
Section: The Traditional Police Approach Stylementioning
confidence: 99%
“…Despite the lack of empirical support for its efficacy, there are a number of common techniques displayed by staff members that are considered to be central to effective de-escalation strategies. These include interpersonal skills, authentic engagement, calm and controlled communication, the ability to assess the initial situation, and demonstrating a collaborative approach to problem solving (Johnson andDelaney 2007, Finfgeld-Connett 2009). It is argued that the most common mistake made in such situations is for the staff member to lose their composure and act in an authoritarian or otherwise disbelieving way (Maier 1996).…”
Section: The Management Of Aggression In Psychiatric Servicesmentioning
confidence: 99%